Acipenser baeri Brandt 1869 ... - Litz, Thomas O.; The, Stefan Koerber Introduction (Zenodo, 2014)
A. baeri Brandt, 1869 NT first record Nion et al. (2002) remarks introduced exotic species! origin Northeastern Asia; Arctic rivers of Europe and Siberia ... : Published as part of Litz, Thomas O. & The, Stefan Koerber Introduction, 2014, Check List of the Freshwater Fishes of Uruguay (CLOFF-UY)., pp. 1-40 in Ichthyological Contributions of PecesCriollos 28 on page 5, DOI: 10.5281/zenodo.11558256 ...